La congiura di Kafka (Materiali di Estetica. Terza serie, 2025)
This brief essay reads Franz Kafka’s letters to Milena Jesenská around the motif he calls his “inner conspiracy,” a destabilizing impulse that would overturn the rule-bound determinism of existence – figured through the game of chess – by suspending causal necessity. In imagining a game where one steps outside the board like an arbiter-God (Kafka flirts with a Spinozist register), determinate moves yield to radical contingency: every piece, every destiny exposed to chance. Kafka is at once drawn to and horrified by this prospect, while Milena’s own vulnerability sharpens the ethical stakes the “conspiracy” opens.
Keywords: Milena Jesenská; inner cospiracy; Spinoza